Withdrawn Behavior in Preschool: Implications for Emotion Knowledge and Broader Emotional Competence - Clark, Samantha E.; Locke, Robin L.; Baxendale, Sophia L.; Seifer, Ronald (Frontiers in Psychology, 2022)
The present study investigated the respective roles of withdrawal, language, and context-inappropriate (CI) anger in the development of emotion knowledge (EK) among a subsample of preschoolers. Measures included parent-reported withdrawn behavior, externalizing behavior, and CI anger, as well as child assessments of receptive language and EK. Ultimately, findings demonstrated that receptive language mediated the relationship between withdrawn behavior and situational EK. However, CI anger significantly interacted with receptive language, and, when incorporated into a second-stage moderated mediation analysis, moderate levels of CI anger rendered the indirect effect of withdrawn behavior on situational EK via receptive language insignificant. Cumulatively, these findings demonstrate a mechanism by which withdrawal may impact EK. They also indicate that such an effect may be attenuated in children with moderate levels of CI anger. Implications of these findings are discussed.